The Last castle - Lawrence, Robert; Lurie, Rod (DreamWorks, 2001)
Robert Redford, goes up against a ruthless prison warder in this powerhouse action thriller. His service to his country made him a hero. One mistake made him a prisoner. For General Eugene Irwin, it's just a matter of serving out his sentence - until he makes the shocking discovery that his fellow inmates are being murdered. Now, Irwin is taking command one last time - and unifying the inmates in a desperate battle to overcome a brutally corrupt system and show the world the truth.